Profile of Hiperdia patients in the municipality of Barra Bonita, Sao Paulo state - Camila Gimenes; Thalita Maximo Lopes Tinoco; Alberto de Vitta; Eduardo Aguilar Arca; Bruna Varanda Pessoa-Santos; Silvia Regina Barrile
Abstract Introduction: The "Hiperdia System" sets goals and guidelines to expand prevention, diagnosis, treatment and control of Diabetes Mellitus and Hypertension. Knowing the epidemiological characteristics of the population is important to strengthen public health programs. Objective: The objective of the study was to describe the sociodemographic profile, risk factors and complications of hypertensive, diabetic and hypertensive diabetic people registered in the HiperDia system of the Ministry of Health of the Basic Health Units (Unidades Básicas de Saúde - UBS) in Barra Bonita, São Paulo State. Methods: This is a descriptive cross-sectional study, which used 113 medical records of diabetic and hypertensive patients as a data source for information about gender, age, race, education, marital status, body mass index (BMI), family history, smoking, sedentarism, acute myocardial infarction, stroke, kidney disease, amputation and diabetic foot. Descriptive statistics were used. Results: As a result, the epidemiological profile of patients registered in the HiperDia system was characterized by: a mean age of 57.3 years; 61.9% women, 82.1% Caucasians, 66.4% with education level up to incomplete primary education, 48.5% lived with partners and children, 19.5% were smokers, 51.4% were sedentary, 44.3% were overweight and obese and 69% had a diagnosis of hypertension and diabetes. Conclusion: The results were relevant allowing professionals and health managers to institute preventive programs to intervene in the risk factors involved in the genesis and complications of hypertension and diabetes.